MODEL KARYAWISATA DALAM IMPLEMENTASI KURIKULUM MERDEKA (STUDI KASUS PERGURUAN TINGGI DI KABUPATEN PANDEGLANG) - Desyi Rosita; Agus Hidayatullah; Nurkhairina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to identify, describe, and evaluate the effectiveness of the field trip model in supporting the implementation of Merdeka Belajar Curriculum in Pandeglang Regency Colleges. This research uses a qualitative approach with a case study method, involving students and lecturers in universities in Pandeglang Regency as research subjects and objects. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis was carried out by document study, interviews, discussions, and observations. The results showed that the implementation of the field trip model made a significant contribution to the success of the Merdeka Belajar Curriculum. This model allows integration between theory and practice, and provides relevant and meaningful field-based learning experiences. In addition, field trips also support the development of non-academic skills such as critical thinking, creativity, collaboration, and leadership. Constraints encountered include limited budget, facilities, as well as administrative and logistical barriers. Proposed solutions include collaboration with external partners, selection of affordable locations, careful planning, and utilisation of digital technology for more efficient coordination. Overall, this study indicates that the field trip model is effective in improving students' learning motivation, academic and non-academic skills, and supporting adaptive learning objectives relevant to 21st century skills.